Analisis Pemasaran AJB Bumiputera 1912 Kantor Wilayah Medan - Thasya Virdinia; Maryam Batubara (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This research aims to analyze the marketing strategy of AJB Bumiputera 1912 at the Medan Regional Office by considering various aspects such as market segmentation, promotional strategies, product distribution, premium policies and customer response. The research methods used include literature observation, analysis of internal company data, and interviews with relevant stakeholders. The research results show that the company has succeeded in identifying responsive market segments, implementing various promotional strategies, and building an extensive distribution network. However, there is room for improvement in each aspect of marketing. This analysis provides a strong basis for developing more effective marketing strategies in the future, with the hope of improving company performance and maintaining competitiveness in an increasingly competitive insurance market. The conclusions of this research provide comprehensive insight into the challenges and opportunities faced by AJB Bumiputera 1912 in the Medan Regional Office in optimizing their marketing strategy to achieve sustainable business goals.